Enhancing Patient Services Management Through Interdepartmental Integration And Digital Health Solutions In General Hospitals - Hani Mukhled Alotaibi, Abdullah Banaider Alharthi, Ziad Aboud Alotaibi, Ibrahim Yayah Almakrami, Mohammed Ali Al Mujri, Mohammed Khalid Alhumaid, Nawaf Lafyan Alsulami, Salha Jamaan Mufeered And Faisal Abdulrahman Alqahtani (Journal of International Crisis and Risk Communication Research, 2024)
General hospitals are experiencing a proliferation of digital health solutions—including electronic health records, telemedicine, remote monitoring, patient triage, scheduling, portals, and artificial intelligence—that can improve patient services management. Even as the urgency created by the COVID-19 pandemic has abated, many of these technologies continue to attract attention as institutions recognize their potential to strengthen pre-, intra-, and post-treatment processes. In parallel, a growing body of literature highlights the importance of interdepartmental integration, defined as synchronized workflows and coordinated information sharing across hospital service lines and clinical and non-clinical units. Isolationism can impede the smooth flow of patients through the hospital, negatively affecting wait times, throughput, safety, and other key performance indicators. Underlying the urgency of the topic is a recognition that the emergency, outpatient, and inpatient stages of patient flow are increasingly linked, and that hospitals now routinely manage a wider range of service lines and treatment modalities. These changes are fostering vitality in the intertwined digital health and interdepartmental integration agendas. While both digital health solutions and interdepartmental integration hold promise for improving patient services management, many general hospitals lack a comprehensive picture of the current state of the former curriculum and their specific needs in the latter. Hospitals interested in strengthening patient services management therefore face two main questions: What is the existing portfolio of digital health solutions, and what patient services management issues are likely to be most pressing? What are the main interdepartmental integration models and mechanisms, and how might these apply to patient services management? Answering these questions can provide a foundation for empirical studies that assess the potential of digital health solutions and interdepartmental integration (Klumpp et al., 2022) (Snowdon et al., 2024) (van de Wetering, 2021).